LEGALITAS DAN PEMANFAATAN TEKNOLOGI BLOKCHAIN TERHADAP SMART CONTRACT PADA PERJANJIAN BISNIS DI INDONESIA - Rukman, Juliana Ananda (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2025)
Abstract: The development of digital technology has encouraged various companies to innovate, one of which is by utilizing blockchain in smart contract systems. This technology, derived from cryptocurrency, enables transactions to run automatically through programmed code that translates into legal language. This study aims to examine the legitimacy of blockchain technology in supporting smart contracts as digital legal instruments and to analyze its application in business agreements between entrepreneurs in Indonesia. This research uses a normative juridical approach that focuses on analyzing relevant legal provisions. The results show that this technology has great potential to simplify transaction systems and reduce costs. However, its application requires adjustments to the legal system and social acceptance to function optimally and provide adequate legal protectionKeywords: Blockchain, Smart Contract, Legalitas, Perjanjian Elektronik